Implementasi Kurikulum Berbasis Cinta pada Mata Pelajaran IPS: Tinjauan Psikologis Perkembangan Emosional Anak Usia Madrasah Ibtidaiyah Assalam 4 Bajo - Hidayatul Musthofa (PEDAGOGIA : JURNAL KEGURUAN DAN PENDIDIKAN, 2026)
This research is motivated by the affective crisis that occurs in the madrasah environment, including low regulation of emotions, empathy, and psychological well-being of students, while the implementation of the Love-Based Curriculum (KBC) in social studies subjects has not been optimal. This study aims to describe the implementation of KBC in social studies subjects, analyze the emotional development of children of madrasah ibtidaiyah age, and examine the influence of KBC implementation on the emotional development of students at MI Assalam 4 Bajo. This research uses a qualitative approach with a case study type. The main data sources consisted of madrasah heads, three social studies teachers, and twelve students in grades III, IV, and V who were selected by purposive sampling. Data were collected through eight weeks of passive participatory observation, in-depth interviews, and document analysis of learning tools. The results of the study show that the implementation of KBC at MI Assalam 4 Bajo is still partial and non-systemic, characterized by the lack of integration of love values in the lesson plans, syllabus, and learning process. Students' emotional development is relatively low in the aspects of emotional regulation, empathy, and emotional well-being. There was a correlation between weak integration of love values and poor emotional development of students, where classes with an authoritarian approach showed higher levels of aggressiveness and absenteeism, while sporadic caring behavior of teachers had only limited impact. This study concludes that the implementation of systemic KBC is very necessary to improve the emotional development conditions of students.